Atlantic urban transfers in early modernity: Mazagão, from Africa to the Americas - Correia, Jorge (2013)
The history of the Portuguese city of Mazagão is also the history of a journey over the Atlantic. Designed and settled in 1541 in Northwest Africa, the motivation for the grid layout of this fortress-city may be interpreted as a compromise between the urban knowledge developed in neighboring examples of occupation by conquest and the aspiration of an “ideal” model. The Portuguese were to remain here until 1769 when Mazagão was abandoned and its population transferred to the Amazon basin where New Mazagão was founded. This time, a geometrical regular plan was carried along by these colons as well as their African religious traditions, strikingly still present nowadays. More than a direct spatial translation from Africa to South America, this journey allows us to analyse the Portuguese contribution to the urban design and public space from the 16th to the 18th centuries along the coasts and islands of the Atlantic and its differences to the Hispanic world. The Portuguese urban experience though the 500s can be told by the application of reason to fabrics with regular propensity together with a case by case assessment of the conditions for that application, and not through an abstract plan as in the Laws of the Indies. Mazagão, together with Angra (Azores) and Salvador (Brasil), showing both a tendency to regular urbanism and a voluntarily Renaissance aspiration, were harbors for the Portuguese expansion al romano urban experience. The history of Mazagão’s journey over the Atlantic can be related as an urban transfer, rather than an urban translation. In fact, important cultural flows were the key element for the keeping of urban activities that can be observed in similar dimensions throughout Early Modernity and Transatlantic territorial spheres. Through case studies shown in this article, the Portuguese urban practice related to regularity can be demarked between a laboratorial example of mathematics application and a mature model of knowledge exportation in the age of the Lights.